LOCALIZATION OF TIGHT JUNCTIONS BETWEEN TANYCYTE-LIKE CELLS OF THE SULCUS MEDIANUS ORGANUM IN RAT BRAIN (Iraqi Journal of Medical Sciences, 2017)
Background: Tanycytes are highly specialized ependymal cells (ECs) that line the regions of circumventricular organs (CVOs) where the blood-brain barrier is absent. These cells show tight junctions (TJs) that form a blood–cerebrospinal fluid barrier at the regions of these organs, thus modulating the transport mechanisms between the cerebrospinal fluid and the brain capillaries. Objective:To investigate the presence of TJs between ECs of the sulcus medianus organ (SMO) in the floor of the 4th ventricle in comparison to the region of the median eminence (ME) of the hypothalamus, a known CVO in the brain.Methods: Ten adult male rats (Rattus Norvegicus Albinus) aged 3-6 months were used to study the general histological morphology of ECs at the SMO and ME regions by H. and E. stain, and to explore the immunofluorescence labelling of these cells for TJs using anti-ZO1 FITC.Results: The ECs were arranged in 2-3 layers in the depth of the median sulcus (MS) at the SMO region as seen with H. and E. stain. Immunofluorescent labelling with anti-ZO1 FITC revealed the presence of TJs between ECs of the SMO in a way similar to that reported between tanycytes of the ME.Conclusion: The SMO contained tanycytes or tanycyte-like cells that exhibited TJ complexes. This unique cell population added a strong evidence for the presence of a CVO in the rostral part of the MS to link CVOs on both sides of the cerebral aqueduct.Keywords: Tanycytes, circumventricular organs, sulcus medianus organum, tight junctionsCitation: Fadhil H. Ahmed, Muthanna A. Al-Kaabi, Sarmad E. Al-Marsoummi, Hayder A. Al-Aubaidy. Localization of tight junctions between tanycyte-like cells of the sulcus medianus organum in rat brain. Iraqi JMS. 2017; Vol. 15(1): 48-63. doi: 10.22578/IJMS.15.1.7
Keywords: Tanycytes; circumventricular organs; sulcus medianus organum; tight junctions